Biochemical and physical characterizations of fish protein isolate and surimi prepared from fresh and frozen whole fish. (April 2017) - Kobayashi, Yuka; Park, Jae W.
Abstract: The effect of frozen storage on the biochemical and physical characterization of fish protein isolate (FPI) and surimi made from tilapia was elucidated: tilapia frozen for 3 mo can be used like fresh fish in the processing of FPI and surimi. The Ca 2+ ATPase activity continuously reduced throughout the frozen storage up to 3 mo; however, the diminishing trend of Ca 2+ ATPase activity was slow. According to storage modulus (G′), storing whole fish frozen for 3 mo did not affect the gelling ability of FPI and surimi with 0% salt. The comparable results were observed by surface hydrophobicity, surface reactive sulfhydryl content, and differential scanning calorimetry. The addition of salt into FPI induced higher degrees of denaturation before gelation compared to surimi. Our results suggested that frozen tilapia, if stored up to 3 mo, can be used to make good quality FPI and surimi. Highlights: Good quality fish protein isolate (FPI) and surimi can be made from 3-mo frozen tilapia. FPI was more sensitive to salt addition and heating than surimi based on the degree of unfolding. The effect of salt on gelation is different between FPI and surimi made from tilapia.